Radiation-Induced Vascular Disease—A State-of-the-Art Review - Yang, Eric H.; Marmagkiolis, Konstantinos; Balanescu, Dinu V.; Hakeem, Abdul; Donisan, Teodora; Finch, William; Virmani, Renu; Herrman, Joerg; Cilingiroglu, Mehmet; Grines, Cindy L.; Toutouzas, Konstantinos; Iliescu, Cezar (Frontiers in Cardiovascular Medicine, 2021)
Since the 1990s, there has been a steady increase in the number of cancer survivors to an estimated 17 million in 2019 in the US alone. Radiation therapy today is applied to a variety of malignancies and over 50% of cancer patients. The effects of ionizing radiation on cardiac structure and function, so-called radiation-induced heart disease (RIHD), have been extensively studied. We review the available published data on the mechanisms and manifestations of RIHD, with a focus on vascular disease, as well as proposed strategies for its prevention, screening, diagnosis, and management.